Manajemen Sumber Daya Manusia Dalam Pendidikan Islam : Strategi Dan Tantangan - Rusmita; Jamilus (Jurnal Manajemen DIVERSIFIKASI, 2024)
Islamic education has a central role in forming individuals who not only understandreligion, but also have morals and personality that are in accordance with Islamicteachings. Human resource management (HR) in Islamic educational institutions hascomplex challenges, both from an external and internal perspective. This article investigatesvarious aspects of HR management in the context of Islamic education, starting from basicconcepts, development processes, strategies to the challenges that may be faced. The studymethod uses a library research approach, with data analysis carried out qualitatively. Theresults of the study show that human resource development in Islamic educationalinstitutions requires a continuous process of planning, organizing, directing andmonitoring. A holistic management strategy, including recruitment, employee development,leadership, performance management, technology and collaboration, is the key to success.External challenges such as technological developments, demographic changes, socio-cultural dynamics, economic factors, as well as legal and political changes, influence HRmanagement. Quick response and effective internal management are needed to keep Islamiceducational institutions relevant and of high quality. Good HR management will support theachievement of the goals of Islamic educational institutions in forming individuals who arein accordance with Islamic values